Аge and gender characteristics of vitamin D status in patients with type 2 diabetes mellitus during the full-scale war in Ukraine - M.I. Bobryk; Y.I. Komisarenko (Bolʹ, Sustavy, Pozvonočnik)
Background. Considering the changes in the population’s lifestyle during the russian-Ukrainian war, it is relevant to study vitamin D levels in patients with type 2 diabetes mellitus (T2DM) in dynamics during the war. The study aimed to assess the status of vitamin D in different age and sex groups of patients with T2DM during the full-scale war in Ukraine compared to the pre-war status. Materials and methods. In 2021–2024, a study of 1256 patients with T2DM aged 19–75 years. Vitamin D status was assessed by measuring serum levels of 25-hydroxyvitamin D (25(OH)D) in the morning on an empty stomach using an immunochemiluminescent method. Results. The level of (25(OH)D) in 2021 was significantly higher in all age categories of patients with T2DM and corresponded to vitamin D insufficiency. For the age category 25–44 years, significantly lower levels of 25(OH)D were found in 2022, 2023 and 2024 compared to those examined in 2021. For the age category 45–59 years, the average level of 25(OH)D in 2022 was lower compared to other periods. For the age category 60–75 years, the average level of 25(OH)D in 2023 was lower than in 2024. In the youngest group of patients aged 19–24 years, 25(OH)D levels ranged from 38.7 to 77.4 nmol/L, covering both D deficiency and D insufficiency found during 2021–2024. The 60–75 age group had the highest mean 25(OH)D level in 2024: 73.3 nmol/L. The mean 25(OH)D level in women with T2DM in 2024 was slightly higher than in men. Conclusions. 25(ОН)D level in 2021 was significantly higher in all age categories of patients with Т2DM compared to 2022–2024 and corresponded to vitamin D insufficiency. The highest average level of 25(ОН)D in 2024 was in Т2DM patients aged 60–75 years.